Um Exerci{dotless acute}cio Filosófico sobre a Pesquisa em Educação Matemática no Brasil - Bicudo, Maria Aparecida Viggiani [UNESP]; Paulo, Rosa Monteiro [UNESP] (My University, 2011)
In this research we present a meta-comprehension about the research on Mathematics Education developed in Brazil through an hermeneutical analysis of the texts presented and discussed on the III SIPEM - International Seminar on Mathematics Education occurred on 2006. We present the trends that were identified in the research and emphasize the interrogations, questions and problems they address as well as their scientific, philosophical, and methodological rigor. We present the nucleus of ideas present in Mathematics Education research in Brazil as we transcend the individual production of research, focusing on the references of national and international authors. We conclude that the research analyzed has been clearly designed, introducing conceptions of and ways of working with Mathematics that address issues related to education, society, culture, teaching, learning, and history of Mathematics Education.
A philosophical study of research in mathematics education in Brazil
Keywords: Hermeneutical analysis; Mathematics education; Phenomenology; Research